SKRINING KELENGKAPAN RESEP BPJS DI APOTEK SANA FARMA KOTA MAKASSAR - Agust Dwi Djajanti; Rusmin Rusmin (Akademi Farmasi Yamasi Makassar, 2022)
A prescription is a written request for medicine from a doctor to a pharmacist, to provide and administer medicine to a patient. There are 3 aspects that must be considered in conducting prescription screening, namely pharmaceutical aspects, administrative aspects and clinical aspects. One very important aspect is the administrative aspect where this aspect includes all patient information and the types of drugs that doctors prescribe. the function of the administrative aspect is to minimize the occurrence of medication errors. The purpose of this research was to determine the percentage of completeness of BPJS prescriptions at the Sana Farma Pharmacy according to the regulation of the Minister of Health number 73 of 2016 and pharmaceutical technical instructions at the pharmacy. This type of research includes descriptive observational research. The number of samples used was 553 prescription sheets. Based on the research that has been done, the percentage of incomplete prescriptions includes: the inscriptio section including doctor's name 8,10%, SIP 19,71%, doctor's address 0,29%, doctor's telephone number 7,38% and date of prescription writing 10,34%. in the invocatio section including the R / complete mark. in the prescription section, including the name of the drug, the dosage form and the amount requested, all are complete. in the signature section including the rules for drug use, drug dosage, route of administration and intervals, all are complete. in the Pro section, the patient's name is 0,22%, the patient's age is 12,15%, the patient's address is 17,50%, the patient's weight is 19,42% and the gender is 0,22%. as well as in the subscriptio including initials/signatures of doctors 1,86%.